The Effectiveness of Using Some Active Learning strategies on the development of grammatical skills of eighth grade female students in the Republic of Yemen - Al-Wajih, Haifa Ali (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to know the impact of using some active learning strategies in the development of grammatical skills of eighth grade female students in the Republic of Yemen, To achieve this goal, the researcher used descriptive and semi-experimental methodologies, It prepared a list of grammatical skills, an achievement test, and an educational program according to active learning strategies, The research sample consisted of (80) students from the eighth grade basic students in the Capital Secretariat, who were deliberately selected, It was divided into two groups: the first was experimentally studied using active learning-based software, and the second was studied using the usual method, The research results showed the following: -Statistically significant differences exist at the significance level (0.05) between the average grades of the students of the experimental and control groups in the dimensional application of the grammatical skills test in favor of the experimental group. - The presence of statistical function differences at the function level (0.05) between the average grades of the students of the experimental group in the tribal and post- applications of the grammatical skills test in favor of the dimensional application.